Recurrence of a second-trimester uterine rupture in the fundus distant from old scars: A case report and review of the literature - Anne-Claude Fahrni; David Salomon; Antonio Zitiello; Anis Feki; Nordine Ben Ali (Elsevier, 2020)
Uterine rupture is a rare event which can have severe obstetric consequences and most often occurs on a scarred uterus at the site of the scar. However, a uterine rupture can appear at another location. We report the case of a woman with a previous emergency caesarean section for spontaneous posterior uterine rupture which recurred at another site during her second pregnancy. She was admitted to the emergency room with acute abdominal pain and development of a pre-shock hemorrhagic state. Abdominal ultrasound showed abundant peritoneal fluid and a fetus without cardiac activity in an intact bulging amniotic fluid membrane. We performed an emergency laparotomy, which confirmed an intact amniotic sac in the abdominal cavity and showed a 7 cm transverse fundal uterine rupture beginning at the right angle, distant from the old known scars. In view of the high maternal and fetal morbidity, obstetricians should have a high suspicion of an antepartum uterine rupture, even at an early gestational age, in the event of acute abdominal pain over a scarred uterus.